Application of a quantitative HPLC-ESI-MS/MS method for flavonoids in different vegetables matrices - Perlatti, Bruno; Fernandes, João B.; Silva, Maria F.G.F.; Ardila, Jorge A.; Carneiro, Renato L.; Souza, Bruno H.S. [UNESP]; Costa, Eduardo N. [UNESP]; Eduardo, Wellington I. [UNESP]; Boiça Junior, Arlindo L. [UNESP]; Forim, Moacir R. (Sociedade Brasileira de Quimica (SBQ), 2016)
Plant favonoids have been increasingly studied for its importance in plant metabolism, interspecies interactions and human health-promoting effects. Each botanical species has a distinct favonoid profle, and as such, this work aimed to develop and apply a high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) method to quantify specific favonoids in different plants and parts. Six favonoids (isoquercitrin, quercetin, naringin, naringenin, hesperidin and rutin), two isofavonoids (daidzin and daidzein) and one coumarin (umbelliferone) were targeted. Calibration curves showed good correlations (R2 > 0.994) and limits of quantification (≤ 500 ng mL-1). The method was applied for detection of analytes in common bean seeds (Phaseolus vulgaris), soybean leaves (Glycine max), and sour orange (Citrus aurantium), sweet orange (Citrus sinensis), and Tahiti lime (Citrus latifolia) favedo after ultrasound assisted acidic hydroalcoholic extraction. The method was tuned for quick and efficient extraction. Principal component analysis was helpful for the discrimination of matrices based on their favonoid profles.
Keywords: Favonoid; HPLC-ESI-MS/MS; Quantitative analysis